Still the lands of equality? On the heterogeneity of individual factor income shares in the Nordics - Roberto Iacono; Elisa Palagi (Global Labor Organization (GLO), 2020)
As far as standard measures of income inequality are concerned, the Nordic countries rank among the most equal economies in the world. This paper studies whether and how this picture changes when the focus is on inequality of income composition, meaning the heterogeneity in individuals' factor income shares. We highlight the structural change taking place in all the Nordic countries since the early 1990s, with rising inequality in composition of individual incomes due mostly to a shift in capital incomes towards the top of the distribution. We link this result to changes in taxation of factor incomes, by highlighting the role played by the introduction of Dual Income Taxation reforms in the 1990s throughout the Nordic countries. Our estimates of the degree of income composition inequality allow a descriptive analysis of the role of functional distribution as a determinant of personal income inequality in the Nordics. We show that for Denmark in the period 2009-2013, Finland 1990-2007, and Norway 1991-2005, rising capital shares of income contributed to changes in personal income inequality, whilst for Sweden the evidence leads to disregard the capital share as a determinant of income inequality.
Keywords: D33; D63; E25; D31; 330; dual income taxation; income composition inequality; Nordic countries